Rhus coriaria L. Fruit Extract Prevents UV-A-Induced Genotoxicity and Oxidative Injury in Human Microvascular Endothelial Cells - Emma Nozza; Gloria Melzi; Laura Marabini; Marina Marinovich; Stefano Piazza; Saba Khalilpour; Mario Dell’Agli; Enrico Sangiovanni (Antioxidants, 2020)
Rhus coriaria L. (sumac) is a small plant widely diffused in the Mediterranean region. Its fruit are often consumed as a spice but are also present in traditional medicine of several countries. Recently, interest in this plant has increased and many scientific works reported its beneficial effects including antioxidant and anti-inflammatory properties. Plant extracts can be successfully used against ultraviolet rays, which are able to reach and damage the human skin; however, sumac extracts were never applied to this usage. Thus, in this study, we used a macerated ethanol extract of Rhus coriaria L. dried fruit (mERC) to demonstrate its preventive role against the damage induced by ultraviolet-A rays (UV-A) on microvascular endothelial cells (HMEC-1). In vitro effects of the extract pre-treatment and UV-A exposure were evaluated in detail. The antioxidant capacity was assessed by reactive oxygen species (ROS) formation and cellular antioxidant activity measurement. Genoprotective effects of mERC were investigated as well. Our findings indicate that the extract acts as a cell cycle inhibitor or apoptosis inducer, according to the level of damage. The present work provides new insights into the usage of Rhus coriaria extracts against skin injuries.